THE USE OF MODERN INNOVATIVE TECHNOLOGIES AND METHODS IN TEACHING A FOREIGN LANGUAGE AND THEIR EFFECTIVENESS (American Journal of Technology and Applied Sciences, 2023)
This article discusses innovative technologies in teaching foreign languages and their role in the field of Education.